2016
DOI: 10.1007/s11012-016-0450-y
|View full text |Cite
|
Sign up to set email alerts
|

Revisited modelling and multimodal nonlinear oscillations of a sagged cable under support motion

Abstract: Sagged cable vibrations caused by support motion and possible external loading are investigated via the four-degree-of-freedom model proposed in Benedettini et al. (J Sound Vib 182(5):775-798, 1995). The model has a considerable potential in terms of forcing cases to be possibly addressed, with the physical motion of the supports naturally giving rise to a variety of external and parametric excitation terms. Dynamics of the system is studied close to the multiple internal resonance at cable crossover, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In addition, Rega et al [1], Nayfeh et al [2], and Benedettini et al [3] adopted the multiple scaled method to analyze the nonlinear vibration of hangers in suspension bridges qualitatively and quantitatively. Subsequently, Warminski et al also used a multiple-scale method to study the four-degree-of-freedom model of cables, verified the analytical results by numerical simulation results, and found that under a higher excitation amplitude, a multipeak response might appear [16]. Srinil et al investigated the planar 2 : 1 resonance of the stayed cables using the multiple-scale method and the Galerkin method and found that the finite element solution agreed well with the response calculated by the approximation of the Galerkin method [17].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Rega et al [1], Nayfeh et al [2], and Benedettini et al [3] adopted the multiple scaled method to analyze the nonlinear vibration of hangers in suspension bridges qualitatively and quantitatively. Subsequently, Warminski et al also used a multiple-scale method to study the four-degree-of-freedom model of cables, verified the analytical results by numerical simulation results, and found that under a higher excitation amplitude, a multipeak response might appear [16]. Srinil et al investigated the planar 2 : 1 resonance of the stayed cables using the multiple-scale method and the Galerkin method and found that the finite element solution agreed well with the response calculated by the approximation of the Galerkin method [17].…”
Section: Introductionmentioning
confidence: 97%
“…Equilibria and dynamics of cable systems continue to be studied until today as it is reported in the detailed review of Rega [3] with a focus on the modal analysis and the dynamics of cable systems. The temporal evolution of these systems is treated with different approaches in the literature, for instance via the time integration of a linearized system [4] or via studying reduced-order models before comparing them to results traced by a full Finite Element Method (FEM) as done by Gatulli et al [5] which topic was revisited later with a comparison to the projected dynamics time integration by Warminski et al [6]. Other theoretical developments have also been carried out for studying statics of cable systems when more sophisticated equilibria are considered, for example, with an intermediary pulley [7], for the dynamics of transmission lines by Tsui [8,9] and also for galloping phenomena studies via FEM by Desai et al [10] or even for a cable network [11].…”
Section: Introductionmentioning
confidence: 99%
“…A method of multiple scales have been endowed by Warminski and al. [16] to trace the bifurcations of a reducedorder model accounting for cable dynamics. Ferreti and al.…”
Section: Introductionmentioning
confidence: 99%